Study of Product and Price Management in Marketing Moringa Tea: (Case of U.D. Wuna Barakati in Muna Regency, Southeast Sulawesi Province) - Alimin, Alimin; Supiani, Supiani (Jurnal Nasional Manajemen Pemasaran dan SDM, 2024)
U.D. Wuna Barakati is the only Moringa tea producer in Muna Regency. To respond to the increasing competition in the Moringa leaf processed beverage business, this company should completely implement a complete marketing mix strategy and appropriate marketing of its Moringa tea product. However, in the meantime, it seems to have relatively neglected the product mix and price mix strategies. This research examines product and price management in marketing Moringa tea at U.D. Wuna Barakati. Product management refers to implementing a product mix strategy, while price management refers to implementing a price mix strategy. The product mix is assessed from its level but is limited to three levels: Core Benefit Products, Basic Products, and Augmented Products. In contrast, the price mix is evaluated on the basis of the approach used to determine it. Primary data was collected using observation, questionnaires, and in-depth interviews, while secondary data was collected through documentary studies. The data was analyzed descriptively and qualitatively through three main steps: data reduction, data presentation, verification, and conclusion. The research results show that, in general, product mix and price mix strategies are applied to marketing Moringa tea at UD. Wuna Barakti is relatively good. However, several things do not support the competitiveness of the business and need to be improved simultaneously, namely: (a) single product variant, (b) low monthly sales value, (c) prices at the consumer level are relatively high, and (d) the issue of one price policy.